Материалы к систематике, экологии и паразитофауне пресмыкающихся Курильских островов. Сообщение II - Щербак, Н.Н.; Шарпило, В.П. (Вестник зоологии, 1970)
The communication presents data on follidosis, coloration during the life time, nutrition. relation to the temperature and on parasites of Elaphe quadrivirgata and E. cli-macophora.